A comparison between South African and Australian performances on the Australian Talent Search Program - du Randt, R. (2001)
During 1996 the Sports Information and Science Agency (SISA) of South Africa took the first step towards applying a national talent identification strategy. It was decided to emulate the Australian three stage model of talent identification and development even though the limitations of the model were known. The project commenced with the first stage of the talent identification model, which consisted of a mass screening process. The aims of this project were threefold. However, for the purpose of this presentation only the results obtained for the second objective of the study, namely to compare the South African results with that of Australia will be reported on. Originally 1440 subjects from 7 of the 9 South African provinces participated in the project of which 1262 subjects` data were used for further analysis. These subjects ranged between 11 and 16 years of age. The male and female subjects were almost equally represented, with 53% versus 47% respectively. The distribution of advantaged and disadvantaged as well as rural and urban communities was 18%, 82%, 44% and 56% respectively. The screening instrument consisted of 16 tests, 10 of which coincided with the first stage and 3 with the second stage of the Australian talent search test batteries. When comparing the South African and Australian performances in the relevant tests, 78% of the profiles differed significantly (p< 0,05). It was therefore concluded that the Australian selection criteria are not necessarily appropriate to use for the purpose of talent selection in South Africa.